2021
DOI: 10.1121/10.0002951
|View full text |Cite
|
Sign up to set email alerts
|

The impact of face masks on the recall of spoken sentences

Abstract: The effect of face covering masks on listeners' recall of spoken sentences was investigated. Thirty-two German native listeners watched video recordings of a native speaker producing German sentences with and without a face mask, and then completed a cued-recall task. Listeners recalled significantly fewer words when the sentences had been spoken with a face mask. This might suggest that face masks increase processing demands, which in turn leaves fewer resources for encoding speech in memory. The result is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 15 publications
(8 reference statements)
2
35
1
Order By: Relevance
“…In fact, accuracy was at ceiling regardless of whether it was produced with or without a mask. This is in contrast to the Truong et al (2021) study, which found worse cued recall for conversational sentences presented in quiet when a talker wore a mask. This difference could be attributed in part to the mask type and microphone positioning.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In fact, accuracy was at ceiling regardless of whether it was produced with or without a mask. This is in contrast to the Truong et al (2021) study, which found worse cued recall for conversational sentences presented in quiet when a talker wore a mask. This difference could be attributed in part to the mask type and microphone positioning.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparisons of filtering properties of various masks and the effect of mic positions on sound intensity showed that surgical masks provide the best acoustic performance and the lapel mics have smallest signal attenuation ( Bottalico et al , 2020 ; Corey et al , 2020 ; Magee et al , 2020 ). In addition, Truong et al (2021) used short sentences and a cued-recall task, which could have also contributed to the different results found in our study. The combined findings could be used as guidelines for best practices in teaching environments and in clinics.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Although several studies have measured the intelligibility of speech produced with a face mask, they have used either a single type of face mask (Cohn et al, 2021 ; Coyne et al, 1998 ; Mendel et al, 2008 ; Truong et al, 2021 ), a single signal-to-noise ratio (SNR; Bottalico et al, 2020 ; Cohn et al, 2021 ; Coyne et al, 1998 ; though see Toscano & Toscano, 2021 ), or presented speech only in quiet (Magee et al, 2020 ; Truong et al, 2021 ). Given the idiosyncrasies of how different types of face masks alter the acoustic speech signal and possible differences in how this interacts with the level of the background noise, our knowledge of how face masks affect speech understanding would benefit from research manipulating both mask type and noise level.…”
Section: Introductionmentioning
confidence: 99%